National improvements in resident physician-reported patient safety after limiting first-year resident physicians' extended duration work shifts: a pooled analysis of prospective cohort studies. Issue 2 (10th May 2022) - Weaver, Matthew D; Landrigan, Christopher P; Sullivan, Jason P; O'Brien, Conor S; Qadri, Salim; Viyaran, Natalie; Czeisler, Charles A; Barger, Laura K
Abstract : Background: The Accreditation Council for Graduate Medical Education (ACGME) enacted a policy in 2011 that restricted first-year resident physicians in the USA to work no more than 16 consecutive hours. This was rescinded in 2017. Methods: We conducted a nationwide prospective cohort study of resident physicians for 5 academic years (2002–2007) before and for 3 academic years (2014–2017) after implementation of the 16 hours 2011 ACGME work-hour limit. Our analyses compare trends in resident physician-reported medical errors between the two cohorts to evaluate the impact of this policy change. Results: 14 796 residents provided data describing 78 101 months of direct patient care. After adjustment for potential confounders, the work-hour policy was associated with a 32% reduced risk of resident physician-reported significant medical errors (rate ratio (RR) 0.68; 95% CI 0.64 to 0.72), a 34% reduced risk of reported preventable adverse events (RR 0.66; 95% CI 0.59 to 0.74) and a 63% reduced risk of reported medical errors resulting in patient death (RR 0.37; 95% CI 0.28 to 0.49). Conclusions: These findings have broad relevance for those who work in and receive care from academic hospitals in the USA. The decision to lift this work hour policy in 2017 may expose patients to preventable harm.